Protective Activity of 1, 8-Cineole against Inflammatory and Oxidative Stress Marker from Methyl Methacrylate Exposure - Sianiwati Goenharto (Journal of Global Pharma Technology, 2016)
Objective: This study was aimed to determine the potential of 1,8-cineole to reduce the amount of malondialdehyde (MDA), interleukins (IL)-8 and neutrophils in MMA-exposed lung alveolar cells. Methods: Thirty mice were divided into five groups: a normal control group (K0), a negative control group (K1) and a treatment group, further subdivided into P1, P2 and P3, whose members were administered 5 mg, 10 mg and 15 mg doses of 1,8-cineole. The treatment group subjects were placed in a glass cage containing 150 ppm MMA vapor that has been nebulated by 1.8-cineole vapor for 120 minutes. The mice were subsequently terminated, and tissue removed from their lungs. Observation of MDA and expression of IL-8 was conducted during immunohistochemical examination. Neutrophils was observed using Hematoxylin Eosin (HE) staining. Results: MMA exposure significantly increased MDA, IL-8 and neutrophil counts. Meanwhile, administration of 1, 8-cineole successfully reduced MDA numbers. Fifteen milligrams of 1, 8-cineole constituted the only dose which proved capable of reducing the expression of IL-8. Administration of 1, 8-cineole in all groups also decreased the number of neutrophils. Conclusion: 1, 8-cineole, especially at a dose of 15 mg, can reduce the levels of MDA, IL-8 and neutrophil in the lung tissue of mice following exposure to MMA vapor.Keywords: MMA, 1, 8-cineole, Inflammation, ROS, MDA.